Sensitivity of modeled far‐IR radiation budgets in polar continents to treatments of snow surface and ice cloud radiative properties - Chen, Xiuhong; Huang, Xianglei; Flanner, Mark G. (Geophysical Research Letters, 2014)
While most general circulation models assume spectrally independent surface emissivity and nonscattering clouds in their longwave radiation treatment, spectral variation of the index of refraction of ice indicates that in the far IR, snow surface emissivity can vary considerably and ice clouds can cause nonnegligible scattering. These effects are more important for high‐elevation polar continents where the dry and cold atmosphere is not opaque in the far IR. We carry out sensitivity studies to show that in a winter month over the Antarctic Plateau including snow surface spectral emissivity and ice cloud scattering in radiative transfer calculation reduces net upward far‐IR flux at both top of atmosphere and surface. The magnitudes of such reductions in monthly mean all‐sky far‐IR flux range from 0.72 to 1.47 Wm −2 , with comparable contributions from the cloud scattering and the surface spectral emissivity. The reduction is also sensitive to sizes of both snow grains and cloud particles. Key Points Ice cloud and snow surface radiative properties vary considerably in the far IR Snow surface emissivity and cloud scattering affect far IR comparably Even for far‐IR radiation alone, the impact is nonnegligible Peer Reviewed http://deepblue.lib.umich.edu/bitstream/2027.42/109339/1/Auxiliary_material_Aug27.pdf http://deepblue.lib.umich.edu/bitstream/2027.42/109339/2/grl52118.pdf http://deepblue.lib.umich.edu/bitstream/2027.42/109339/3/TableS01.pdf